Within-Track Differentiation and Leisure Activities as Strategies of Distinction - Tim Sawert; Anna Bachsleitner (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2022)
The socially inclusive educational expansion during the last few decades in Germany diluted the previous “elite” status of the Gymnasium and its certificate, the Abitur . In the absence of explicit “elite” institutions, unlike the UK, the USA or France, the question remains how social privilege is intergenerationally transferred in times of educational expansion? Several studies on this topic focused on distinction either through horizontal educational differentiation or via distinctive leisure activities. Building on Bourdieu's theory of distinction and Lareau's study on child-rearing practices, we argue that it is the set of different strategies of distinction that serves as a~mechanism to reproduce privilege. Hence, we ask the question how parents' and grandparents' educational background influences the probability of applying a~whole set of distinctive strategies. To test our assumptions, we use data from the youth questionnaire of the German Socio-Economic panel and analyse the effect of educational background on the application of distinctive educational strategies and distinctive leisure practices and the combination of both domains. The results indicate three main findings: first, having parents with an academic education increases the probability of applying any of the distinctive strategies under consideration. Second, having academically educated grandparents increases the probability of combining distinctive strategies within one domain. Third, the data do not support the assumption that the combination of curricular and leisure practices is particularly socially stratified. – – Die sozial integrative Bildungsexpansion der letzten Jahrzehnte hat in Deutschland den früheren ,,elitären“ Status des Gymnasiums und seines Abschlusses, des Abiturs, verwässert. Da es im Gegensatz zu Großbritannien, den USA oder Frankreich in Deutschland keine expliziten ,,Elite“-Institutionen gibt, bleibt die Frage, wie soziale Privilegien in Zeiten der Bildungsexpansion intergenerationell weitergegeben werden. Mehrere Studien zu diesem Thema konzentrierten sich auf die Distinktion entweder durch horizontale Bildungsdifferenzierung oder durch distinktive Freizeitaktivitäten. Aufbauend auf Bourdieus Theorie der Distinktion und Lareaus Studie zu sozial geschichteten Praktiken der Kindererziehung argumentieren wir, dass es die Gesamtheit der verschiedenen Distinktionsstrategien ist, die als Mechanismus zur Reproduktion von Privilegien dient. Daher stellen wir die Frage, wie sich der Bildungshintergrund der Eltern und Großeltern auf die Wahrscheinlichkeit auswirkt, eine ganze Reihe von Distinktionsstrategien anzuwenden. Um unsere Annahmen zu testen, verwenden wir Daten aus der Jugendbefragung des Sozio-oekonomischen Panels und analysieren die Auswirkungen des Bildungshintergrunds auf die Anwendung von distinktiven Bildungsstrategien und distinktiven Freizeitpraktiken sowie die Kombination beider Bereiche. Die Ergebnisse deuten auf drei wesentliche Befunde hin: Erstens erhöht ein akademisch gebildetes Elternhaus die Wahrscheinlichkeit, eine der betrachteten distinktiven Strategien anzuwenden. Zweitens erhöht sich bei zusätzlich akademisch gebildeten Großeltern die Wahrscheinlichkeit, bestimmte Strategien innerhalb eines Bereichs zu kombinieren. Drittens widerlegen die empirischen Befunde die Annahme, dass die Kombination distinktiver schulischer und Freizeitpraktiken besonders distinktiv ist.
Keywords: 300; Intergenerational mobility; Educational inequality; Effectively maintained inequality; Elite education; Cultural activities; Intergenerationale Mobilität; Bildungsungleichheiten; Elitenbildung; Kulturelle Aktivitäten